Fluvial and pluvial flood hazard mapping: combining basin and municipal scale assessment - Matej Vojtek; Soheyl Moradi; Davide Luciano De Luca; Andrea Petroselli; Jana Vojteková (Geomatics, Natural Hazards & Risk)
In this study, we aimed to assess the fluvial and pluvial flood hazard by a combination of basin and municipal scale assessment using an indicator-based approach, hydrologic-hydraulic modeling, and geographic information systems (GIS). The study area is represented by the Gidra River Basin and 12 municipalities. To calculate a composite flood hazard index (CFHI), we used two components: pluvial flood potential index (PFPI) and fluvial flood hazard index (FFHI). Altogether, five physical-geographical indicators and land use/land cover were used to calculate the PFPI. For determining the FFHI, we calculated three hydraulically modeled indicators for Q100: flood extent, average flow depth, and average flow velocity in each municipality. The most endangered municipalities in terms of the FFHI are located in the central and upper part of the basin while in case of the PFPI, the highest values were obtained by the municipalities located in the lower and central part of the basin. The highest values of CFHI were recorded in municipalities of Cífer, Budmerice, and Jablonec, which are in central part of the studied basin. Reliability of the calculated PFPI and FFHI was proven by the occurrence of past floods in the studied municipalities during the years 1996–2024.